Microencapsulation in the food industry : a practical implementation guide - Gaonkar, Anilkumar G., 1954-; Vasisht, Niraj; Khare, Atul Ramesh; Sobel, Robert (Amsterdam : Elsevier Academic Press, 2014)
Microencapsulation is being used to deliver everything from improved nutrition to unique consumer sensory experiences. It's rapidly becoming one of the most important opportunities for expanding brand potential. Microencapsulation in the Food Industry: A Practical Implementation Guide is written for those who see the potential benefit of using microencapsulation but need practical insight into using the technology. With coverage of the process technologies, materials, testing, regulatory and even economic insights, this book presents the key considerations for putting microenc.
Includes bibliographical references and index.
Keywords: Microencapsulation; Food industry and trade